Strategi Komunikasi Pemasaran Dalam Upaya Meningkatkan Jumlah Room Occuppancy Di Hotel Sulthan Darussalam Pasca Pandemi Covid-19 - Setiawan, Haris; Anas Azhar, Anang; Rozi, Fakhrur (CV. Lafadz Jaya, 2022)
The Covid-19 pandemic has had a huge impact on people's lives, including businesspeople, one of which is in hospitality services. Hotel Sulthan Darussalam is one of the hotels affected by the Covid-19 pandemic. In achieving a success Hotel Sulthan Darussalam has prepared several marketing communication strategies. The purpose of this study was to determine the marketing communication strategy carried out by Hotel Sulthan Darussalam in increasing the number of room occupancy after the Covid-19 pandemic. The research method used in this study uses qualitative research with a descriptive approach using the theory of innovation duffusion and Lasswell. Data collection techniques through interviews and documentation. The results of this study indicate that the marketing communications carried out by Hotel Sulthan Darussalam in the post-Covid-19 pandemic have referred to promotions carried out directly or through social media, maintaining good relations with several companies in collaborating, and offering several facilities via online. travel agent (OTA) to increase the number of room occupancy.